Managerial development activities of RAKUB with special reference to Dhaka corporate branch : a critical appreciation - Shabbir, Rubaiyat (BRAC University, 2016)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Development Management and Practice, 2015.